EFEK MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS DAN TES POTENSI AKADEMIK TERHADAP HASIL BELAJAR FISIKA PADA MATERI OPTIK GEOMETRI - Andar S. Gultom; Nurdin Bukit (Jurnal Pendidikan Fisika, 2013)
The purpose of this research is to determine whether there is anydifference in result of learning physics which is taught with cooperative modeltype STAD model and DI model in grade 10, to determine the effect of thestudent’s academic potential level for the Physics learning outcomes and toknow whether there is an interaction between cooperative learning model typeSTAD and student’s academic potential as the Physics learning outcomes. Thisresearch is a quasi-experiment with two-way design. The population in thisresearch is all students in grade 10 with research sample Class X-1 as the controlclass and Class X-2 as the experiment class which have 32 students in each. Thedata analysis technique used SPSS 17, ANOVA Factorial 2x2. Based on the test performed, it is concluded: there are differences between the Physics learningoutcomes that was taught with cooperative model type STAD and DI model, there was student’s academic potential influence on Physics learning outcomes therewas an interaction between cooperative model type STAD and student’sacademic potential in improving learning outcomes that was show on Schaeffer Test.